CONTRIBUTING FACTORS AFFECTING SPIRITUAL INTELLIGENCE OF NURSES AT BANDUNG HOSPITAL IN INDONESIA - Laili Rahyuwati; Shinta Galih; Efri Widianti; Habsyah Saparidah Agustina; Vira Amelia (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
Background: Nurses are required to conduct themselves professionally at all times, without compromising procedure or the patient's pleasure. Each day, they confront a variety of workplace stresses that might jeopardize their health and possibly result in a reduction or lack of enthusiasm to work. Objectives: The study aimed to determine contribute factors of nurses' spiritual intelligence at Bandung City Hospital based on their characteristics. Methods: This research used a descriptive quantitative method and Spiritual Intelligence of Self Report Inventory (SISRI-24) to collect the data. The respondents were 239 nurses selected using the total population technique. The univariate analysis was used to explain the various levels of spiritual intelligence based on the nurse's characteristics Results: The results show that the nurses' spiritual intelligence in Bandung City Regional General Hospital is 49% high and 51% low. It was also discovered that a high level of spiritual intelligence was based on the following characteristics: aged 41-60 years old, male, and on more- than-10-year tenure, Nursing School graduates, head nurses and nurses assigned at a hemodialysis unit. Conclusion: The research concludes that more than half of the respondents have a low level of spiritual intelligence. Therefore, holding Emotional Spiritual Quotient training is recommended, especially for nurses relatively new to the job. The study has implication because spiritual intelligence is vital in nursing, significantly impacting care quality, well-being of all involved, and leading to better patient outcomes and job satisfaction.